INT-001 Impact of work overload on quality of preparations in chemotherapy. (2nd March 2018) - Carrez, L; Bouchoud, L; Fleury, S; Combescure, C; Falaschi, L; Sadeghipour, F; Bonnabry, P
Abstract : Background: Chemotherapy preparation units have to face an increasing activity with constant staff. Safety is therefore compromised. Purpose: The purpose of our experiment was to measure the effect of a work overload on preparations, accuracy and occurrence of errors. Materials and Methods: Our work was performed in a real working environment using simulated preparations and two tracer drugs (phenylephrine or lidocaine). Twenty-one operators participated in three preparation sessions and had to produce an increasing number of syringes (8, 16 and 24) within a same time period (1 hour). Syringes were assayed by a validated capillary electrophoresis method. Results were analysed according to qualitative (choice of wrong stock solution, diluents and labelling) and quantitative (dose deviation from the target concentration: accurate, <5%; weakly accurate, 5% to 10%; inaccurate, 10% to 30%; wrong, >30%) criteria. Results: A statistically significant decrease in the preparation time per syringe was observed when workload increased (p<0.0001). The average time per preparation was 279 s (95% CI: 246 to 312), 193 s (95% CI: 173 to 214) and 158 s (95%: CI: 138 to 178) for the sessions with 8, 16 and 24 syringes, respectively. The mean accuracy of the doses in the syringes was not statistically different between the three workloads (mean=98.1% (95% CI: 89.6 to 108.6) of the target concentration). The distribution of the doses was: accurate 45% to 51%, inaccurate 23% to 26%, weakly accurate 22% to 29%, and 2% to 4% wrong. Thirty-nine errors of preparations were observed: 30 wrong doses (>30% deviation), six mislabelling, two wrong diluents and one wrong drug. The overall error rate increased with the number of preparations performed in 1 hour: 1.8% for eight preparations, 2.7% for 16% and 5.4% for 24 (p<0.05). The study also showed a strong heterogeneity in the dose accuracy between operators (p<0.0001) and between the preparations for the same operator (p<0.0001). Conclusion: Our study demonstrated that operators can increase their production speed without impacting the mean dose accuracy. However, the acceleration of manual production rate is associated with a greater probability of error's occurrence. These results must strongly encourage cytotoxic production unit managers to take actions to smooth the workload over the day. Acknowledgements: No conflict of interest